Estrus intensity scoring and conception rate in postpartum anestrus buffaloes using estrus induction protocols: Estrus Intensity Score in Postpartum Anestrus Buffaloes - Mishra, Renuka; Bajaj, Nitin Kumar; Shukla, Satya Nidhi; Dhurvey, Madhuri; Bisen, Abhishek Bisen; Maravi, Pushpendra; Vishvakarma, Shashank (Indian Journal of Dairy Science, 2024)
The onset of cyclicity of oestrus cycle and initiation of ovulation during postpartum period in buffaloes constitute a major problem and results into long postpartum anestrus and delayed breeding with consequent serious economic losses in the milk production and efficient reproduction. Effective treatment of postpartum anestrus in buffaloes using estrus induction protocols can efficiently improve their milk productivity. The objective of this study was to compare the estrus intensity score and conception rate in postpartum anestrus buffaloes using estrus induction protocols. Twenty four postpartum buffaloes (5-10 years age) reared under field conditions with the history of not showing signs of estrus for 60 days or more postpartum were considered to be affected with anestrus. These buffaloes were examined per rectally twice at 10 days apart to confirm ovarian activity and genital status. These animals were randomly divided into 4 groups (03 treatment and 01 control group) and each group having 06 anestrus buffaloes. Group I, II and III were treated with CIDR plus Ovsynch, CIDR plus Cosynch and eCG plus Cosynch protocols, respectively, while the control group (Group IV) animals were not given any treatment. The mean weighted oestrus intensity score and conception rate for group I, II, III and IV were 71.33±3.04, 67.66±3.04, 78.33±5.85, 65.00±5.00 and 50.00, 33.33, 66.67 and 33.33 per cent, respectively. It can be concluded that addition of eCG to a GnRH and prostaglandin based protocol (eCG+Cosynch) substantially improved the estrus intensity and conception rates in postpartum anestrus buffaloes.